PRISTINE MANGROVE COMMUNITY IN WONDAMA GULF, WEST PAPUA, INDONESIA - Dharmawan, I Wayan Eka; Widyastuti, Andriyani (Marine Research in Indonesia, 2017)
Papua shoreline has the most extensive area of mangrove in Indonesia. Since this area was rarely studied due to various reasons, the scientific data was difficult to be found. Wondama mangrove, part of Cendrawasih National Park â West Papua, had a promising mangrove forest to be discovered. Preliminary study was carried out in this area to identify how pristine the mangrove area is. The objectives of this study was to analyze mangrove community health and structure. Vegetation structure and canopy coverage data were collected from 107 circular plots included three plot areas (radian: 5 m, 2.5 m and 1 m) which were distributed to determine three plant classes i.e. tree, sapling and seedling, respectively. Present study showed that Wondama mangrove is a pristine mangrove community. It had large size of tree trunk diameter by 19.77Â± 6.55 cm averagely. Its diameter size affected on low tree density which was less than 1000 tree/ha. Those two parameters were strongly negative-correlated each other.Â  On the other hand, community canopy was highly covered mangrove area by 82.46Â±6.43%. Rhizophora has mostly dominated in the forest. Mangrove regeneration in Wondama was excellent referring to density and species composition of sapling-seedling levels.